Determinan kebijakan dividen di Indonesia: good corporate governance (GCG) sebagai variabel intervening - Abriyani Puspaningsih; Rizqi Gusti Pratiwi (Jurnal Akuntansi dan Auditing Indonesia)
The purpose of this study is to investigate the factors that determine the dividend policy. This study also aims to prove the effect of profitabiliy, liquidity, leverage, and growth on dividend policy, through good corporate governance (GCG). The population in this study are included in the rating companies of Corporate Governance Perception Index (CGPI) at 2010 - 2013. The sample selection is done with purposive sampling techniques and criteria used by 36 companies selected. Analysis of the data used multiple linear regression to identify variables that influence the dividend policy and path analysis to detect whether an indirect relationship through GCG and Sobel test use to assess significant for intervening variable. The results of this study showed that profitability gives significant positive effect to the dividend policy, leverage gives significant negative effect to dividend policy, liquidity and growth do not have significant effect to the dividend policy. The implementation of GCG gives significant positive effect on the dividend policy. Profitability and leverage have positive significant impact on the implementation of GCG. Liquidity and growth do not give significant impact to the implementation of GCG. According Path Analysis and Sobel test, the implementation of GCG is the intervening variable to the influence of profitability and leverage on dividend policy.